Biological hard materials abstract - Indrit Vozga (Zaštita Materijala)
Using only precursors commonly available in the environment at ambient temperatures evolution has developed materials with complexity and properties which today’s engineers can only dream of producing. When examining biological hard materials the inclination is to compare the mechanical properties of biological materials with man made materials and to say man made materials are superior in some ways they are. Biology has never come up with materials as hard as silicon carbide, or as strong as steel, but to make these comparisons is to severely misunderstand the materials present in the natural world. The hard materials biology has produced, each of which while not hard by engineering standards, is incredibly complex and performs its role within the organism better than any synthetic material ever could.